Cho P(x) = x3 – 2x + 1 ; Q(x) = 2×2 – 2×3 + x – 5. Tính a) P(x) + Q(x); b) P(x) –Q(x). giup mik vs a 08/08/2021 Bởi Audrey Cho P(x) = x3 – 2x + 1 ; Q(x) = 2×2 – 2×3 + x – 5. Tính a) P(x) + Q(x); b) P(x) –Q(x). giup mik vs a
P (x) = x³ – 2x + 1 Q (x) = 2x² – 2x³ + x – 5 a) P(x) + Q (x) = x³ – 2x + 1 + 2x² – 2x³ + x – 5 = (x³ – 2x³) + 2x² + (-2x + x) + (1 – 5) = -x³ + 2x² – x – 4 b) P(x) – Q(x) = x³ – 2x + 1 – (2x² – 2x³ + x – 5) = x³ – 2x + 1 – 2x² + 2x³ – x + 5 = (x³ + 2x³) – 2x² + (-2x – x) + (1 + 5) = 3x³ – 2x² – 3x + 6 Bình luận
Đáp án+Giải thích các bước giải: a)`P(x)+Q(x)=x³-2x+1+2x²-2x³+x-5` `=(x³-2x³)+(-2x+x)+(1-5)+2x²` `=-x³+2x²-x-4` b)`P(x)-Q(x)=x³-2x+1-2x²+2x³-x+5` `=(x³+2x³)+(-2x-x)+(1+5)-2x²` `=3x³-2x²-3x+6` Bình luận
P (x) = x³ – 2x + 1
Q (x) = 2x² – 2x³ + x – 5
a) P(x) + Q (x)
= x³ – 2x + 1 + 2x² – 2x³ + x – 5
= (x³ – 2x³) + 2x² + (-2x + x) + (1 – 5)
= -x³ + 2x² – x – 4
b) P(x) – Q(x)
= x³ – 2x + 1 – (2x² – 2x³ + x – 5)
= x³ – 2x + 1 – 2x² + 2x³ – x + 5
= (x³ + 2x³) – 2x² + (-2x – x) + (1 + 5)
= 3x³ – 2x² – 3x + 6
Đáp án+Giải thích các bước giải:
a)`P(x)+Q(x)=x³-2x+1+2x²-2x³+x-5`
`=(x³-2x³)+(-2x+x)+(1-5)+2x²`
`=-x³+2x²-x-4`
b)`P(x)-Q(x)=x³-2x+1-2x²+2x³-x+5`
`=(x³+2x³)+(-2x-x)+(1+5)-2x²`
`=3x³-2x²-3x+6`